Naturaleza de la ciencia y género como temas transversales en cursos de Física I de la UNED de Costa Rica - Herrero-Villarreal, Diana; Navarro-Camacho, Marianela; Korach Cascante, Rachel Lyn (Universidad de Costa Rica, 2023)
This article evaluates the incorporation of the theoretical frameworks Nature of Science (NoS) and gender perspective in the course of Physics I at a state university, distance learning, with a population of university campuses from all over the country in the second quarter (May and September) 2022. Strategies were implemented to analyze how science has developed, what have been its internal logics for generating knowledge and the influences of historical and social contexts on its development, emphasizing the participation of women in its construction. The methodological design was mixed, a pre and post-test was applied to 58 students and conversations were held to deepen the results obtained. For the analysis, the differential between the tests and the conversations were obtained and interpreted based on categories established a priori and other emerging ones. The findings show that there are changes in the conceptions of science, in terms of its dynamic nature, the context of justification and discovery. It is possible to understand that social, historical and cultural aspects are involved in the generation of knowledge, however, naive ideas about the scientific method persist. From a gender perspective, the invisibility of women is recognized, the division of labor by sex, a naive position on extraordinary women in science is assumed, and the presence of sexist ideas within scientific theories is not recognized. The women participating in the study achieved greater mobilization towards the expected conceptions of NoS and gender perspective.